Konsentrasi Penyemprotan Natrium Klorida Pada Tandan Buah Segar Kelapa Sawit Terhadap Mutu Minyak Sawit Kasar - Carles Pernando; Fajar Restuhadi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to know the effect of sodium chloride (NaCl) on the quality of fresh palm fruit bunches  and Crude Palm Oil (CPO) also to find the best concentration of sodium chloride.  The method used in this research was a Randomized Block Design (RBD) experiment with six treatments and four replications.  The treatments were NaCl concentrations P0 (0%), P1 (5%), P2 (10%), P3 (15%), P4 (20%), and P5 (25%).  The collected data were statistically analyzed by using Analysis of Variance (ANOVA) continued by Duncan’s New Multiple Range Test (DNMRT) at 5% level.  The parameters observed were loss of brondolan mass, yield, moisture, specific gravity, levels of free fatty acid (FFA), and impurity content. The results of this reseach showed that NaCl can influence the quality of fresh palm fruit bunches that yield the loss of brondolan mass, as well as to the quality of CPO, the levels of  FFA, moisture, and specific gravity.  The treatment chosen from the result of this research was P5 (concentration NaCl of 25%).  Treatment of P5 has levels FFA of 2.05%, moisture 0.216%, impurity content of 0.062%, specific gravity of 0.919, yield of 23.43% and loss of brondolan mass of 2.81%. Keywords: Natrium chloride, fresh fruit bunches, and crude palm oil.